Pregnancy and Sleep Apnea - Mastrodima-Polychroniou, Sofia; Panoulis, Konstantinos (Current Respiratory Medicine Reviews, 2015)
Sleep-disordered breathing (SBD), and especially sleep apnea is prevalent among pregnant women, has numerous medical consequences and is associated with an increased risk of adverse maternal and fetal outcomes. This article is an up-to-date review of pathophysiology, complications, diagnosis and treatment of sleep apnea during pregnancy. Treatment of sleep apnea includes loss of weight, the use of positive airway pressure (CPAP) and the change of sleep position.
Keywords: Continuous positive airway pressure (CPAP)